Crisis of traditional irrigation systems in the Valencian inlands. A case study of Cortes de Pallás: Water landscapes and cultural heritage - Hermosilla Pla, Jorge; Antequera Fernández, Miguel; Iranzo García, Emilio (Documents d’Anàlisi Geogràfica, 2020)
Traditional irrigation systems are a legacy that is manifested through the landscape and hydraulic heritage. The inland areas of Valencia suffer socioeconomic dysfunctions manifested in the landscape. Based on an in-depth analysis of the huerta of Cortes de Pallás situated in the northern area of Macizo del Caroig, we analyze if the processes identified explain the crisis affecting these historical inland irrigation systems. Many plots have been abandoned, even though the morphology and the irrigation system is still functioning.